Xylo-oligosaccharides improve the adverse effects of plant-based proteins on weaned piglet health by maintaining the intestinal barrier and inhibiting harmful bacterial growth - Wang, Qibing; Zhao, Yang; Guo, Lei; Ma, Xiangyuan; Yang, Yi; Zhuo, Yong; Jiang, Xuemei; Hua, Lun; Che, Lianqiang; Xu, Shengyu; Feng, Bin; Fang, Zhengfeng; et al. (Frontiers in Microbiology, 2023)
Introduction Piglets are more susceptible to weaning stress syndrome when fed high levels of plant-based proteins that contain abundant food antigens and anti-nutritional factors. Xylo-oligosaccharides (XOS) are a potential prebiotic that may improve the tolerance of weaned piglets to plant-based proteins. The aim of this study was to investigate the effects of XOS supplementation in high and low plant-based protein diets on growth performance, gut morphology, short-chain fatty acid (SCFA) production, and gut microbiota of weaned piglets. Methods A total of 128 weanling piglets with an average body weight (BW) of 7.63 ± 0.45 kg were randomly allocated to one of the four dietary treatments in a 2 × 2 factorial arrangement, with two levels of plant-based proteins (d 1–14: 68.3 or 81.33%, d 15–28: 81.27 or 100%) and XOS complex (0 or 0.43%) over a 28-day trial. Results The growth performance of piglets did not differ significantly among groups (P > 0.05). However, the diarrhea index of weaned piglets fed a high plant-based protein diet (HP) was significantly higher than that of those fed a low plant-based protein diet (LP) at days 1–14 and throughout the experimental period (P < 0.05). XOS treatment tended to reduce the diarrhea index at days 1–14 (P = 0.062) and during the whole experiment period (P = 0.083). However, it significantly increased the digestibility of organic matter at days 15–28 (P < 0.05). Moreover, dietary XOS supplementation increased ileal mucosa mRNA expression of occludin and ZO-1 (P < 0.05). Furthermore, the concentration of butyric acid (BA) in the cecal contents and in the concentrations of BA and valeric acid (VA) in colon contents were significantly elevated in the XOS groups (P < 0.05). Additionally, XOS optimized the gut flora by lowering the number of pathogenic bacteria such as p_Campylobacterota, thereby stabilizing the gut ecosystem. Discussion In conclusion, the HP diet aggravated diarrhea in weaned piglets while the XOS diet alleviated it by improving nutrient digestibility, protecting intestinal morphology, and optimizing the gut flora.